Education in Early Childhood Prosocial Behavior: Montessori Practical Life Activities at Adinda Daycare in Bandung City - Erni Furwanti; Yanti Krismayanti; Nanin Apriani; Neni Utami Adiningsih (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The planning and implementation of learning in early childhood education still tend not to fully align with children’s developmental stages, particularly regarding the development of prosocial behavior. Limited stimulation and structured programs have resulted in children’s prosocial aspects not developing optimally, necessitating a learning approach better suited to children’s needs. Efforts to develop prosocial behavior have been undertaken at Adinda Daycare, but their effectiveness has not yet been scientifically identified. This study aims to describe the planning, implementation, evaluation, and challenges in applying the Montessori practical life area method to develop prosocial behavior in early childhood. This study employs a qualitative approach using descriptive methods and a case study design. The research subjects are the children at Adinda Daycare who were observed. Data collection techniques included observation, interviews, and documentation using a triangulation approach to ensure data validity. Data analysis was conducted through data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that the implementation of the Montessori practical life area method is effective in improving children’s prosocial behavior including helping others, cooperation, sharing, and honesty to the point where it reaches the “developing as expected” category. Behavioral changes are evident in the increased initiative children demonstrate in helping peers, their ability to cooperate during group activities, their habit of sharing, and their honesty in interactions. Nevertheless, several challenges were identified, such as differences in children’s backgrounds and teachers’ limited understanding of the Montessori method as a whole. The implications of this study suggest that the Montessori practical life method can serve as an effective learning alternative for holistically developing prosocial behavior in early childhood in alignment with their developmental stages.